Site-Specific Seismic Hazard Assessment and Ground Motion Selection for Nonlinear Time History Analysis - Faradina Safiraa; Yuyun Tajunissa; Muhammad Sigit Darmawan; Hendra Wahyudi (Institut Teknologi Sepuluh Nopember, 2025)
This journal aims to study a comprehensive methodology involving Deterministic Seismic Hazard Analysis (DSHA), site-specific ground motion selection, spectral matching, and nonlinear dynamic analysis on Beribis Kendeng Waleri Fault. Seven strong ground motion records were selected from the PEER NGA-West2 database and spectrally matched to the target response spectrum derived from DSHA parameters. Local site effects were incorporated through a site response analysis using detailed subsurface soil data, which classified the site as Class E (very soft soil). The resulting surface-level acceleration time histories were used in nonlinear time history analysis to assess structural performance.